Knowing Is Not Enough: A Mixed-Methods Study of Antimicrobial Resistance Knowledge, Attitudes, and Practises Among Maasai Pastoralists - Mangesho, Peter E.; Caudell, Mark A.; Mwakapeje, Elibariki R.; Ole-Neselle, Moses; Kimani, Tabitha; Dorado-García, Alejandro; Kabali, Emmanuel; Fasina, Folorunso O. (Frontiers in Veterinary Science, 2021)
Global, national, and local efforts to limit antimicrobial resistance often stress the importance of raising awareness among users, sellers, and prescribers of antimicrobial drugs. This emphasis is founded upon two assumptions. First, awareness is limited, particularly concerning the links between antimicrobial use and antimicrobial resistance. Second, “filling the awareness gaps” will motivate practices that will limit antimicrobial resistance. The first assumption is supported by knowledge, attitudes, and practices surveys but these same studies provide mixed support for the second, with several studies finding that knowledge and attitudes are not correlated with related practices. This disconnect may arise as these surveys typically do not collect data on the cultural or historical contexts that pattern antimicrobial use. To explore how these contexts impact knowledge, attitudes and practices related to antimicrobial use and resistance, we use a mixed-methods approach to examine veterinary practices among Maasai pastoralists in Tanzania. We combine a quantitative knowledge, attitudes, and practices survey (N=195 households) with extensive qualitative data from focus group discussions (N=55 participants). Results document limited awareness of antimicrobial resistance but also find that knowledge and attitudes are not correlated with practice. Thematic analysis of qualitative data pointed to three reasons behind this disconnect, including 1) Maasai self-perceptions as veterinary experts, 2) the central role of livestock in Maasai culture, and 3) the use of ethnoveterinary knowledge in animal health treatment. We argue that mixed-methods approaches will be critical to developing the targeted awareness campaigns needed to limit the emergence and transmission of antimicrobial resistance.